Institutionalized overtraining
Overtraining has been of concern to coaches over the past few years since training loads have been increased to the point of often being excessive. The avoidance of overtraining has been a central focus of sports science and sports medicine education . There are two common scenarios with regard to coping with overtraining in sports. 1. If a coach develops an annual plan that includes predicted periods of lessened training stress as a precaution to avoid overtraining or maladaptation, it is possible that athletes will come to expect periods of reduced strain. They usually learn th at they must have such "recovery" periods otherwise they cannot perform well. 2. If a coach frequently quizzes athletes about the symptoms of overtraining or maladaptation, it is possible that athletes will be sensitized to such symptoms and will exaggerate their slightest existence. In more extreme cases, they become neurotic and imagine the symptoms even though they really do not exist at a critical level. Athletes learn to be weaker rather than stronger in the face of continued exercise stress and overtraining symptom emphasis. Both the above illustrations exaggerate the symptoms and onset of overtraining. The institutionally validated emphasis on appropriate symptoms and the state causes athletes to expect to feel stress symptoms, often in a neurotic manner. Some athletes even become obsessed with transitory and minor symptoms, particularly those which originate from stresses outside of the sport. That obsession often becomes strong enough to the point that activity is limited because of the way the athlete feels even th ough assertive activity may be the best therapy to alleviate the outside-of-sport stress symptoms themselves. Thus, the well-meaning coach who does not want to push athletes into excessive and unnecessary long-term fatigue states may actually be producin g a counter-productive psychological state in athletes. An athlete's ability to work to the fullest potential is compromised by anticipations of the symptoms and fear of overtraining. The term "institutionalized overtraining" is used to label this effect. That label recognizes that the origin of the complicating sensitization and expectation is derived from the directing body (i.e., the coach).